Study of the Formation of Artifacts Following Dichloromethane Reaction with Some Nitrogenous Drugs - Mohammadi, Ali; Amini, Mohsen; Pirali Hamedani, Morteza; Heidari Torkabadi, Hossein; B. Walker, Roderick (Asian Journal of Chemistry, 2010)
In this work, the quaternization reaction of some nitrogenous drugs in dichloromethane under stress condition and room temperature at different times are studied. Under these conditions, drug-chloromethochloride adducts or artifacts were found to be formed for clozapine, ofloxacin and olanzapine. The structures of the resultant adducts were elucidated using 1H NMR spectroscopy. In addition, the amount of intact drug was determined using in-house validated HPLC methods with UV detection.